A Model of the Demand for Money by Firms: Comment - Weitzman, Martin (Quarterly Journal of Economics, 1968)
Journal Article A Model of the Demand for Money by Firms: Comment Get access Martin Weitzman Martin Weitzman Yale University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 82, Issue 1, February 1968, Pages 161–164, https://doi.org/10.2307/1882250 Published: 01 February 1968